2021
DOI: 10.1088/1758-5090/ac2209
|View full text |Cite
|
Sign up to set email alerts
|

Combining electrospinning with hot drawing process to fabricate high performance poly (L-lactic acid) nanofiber yarns for advanced nanostructured bio-textiles

Abstract: Fiber constructed yarns are the elementary building blocks for the generation of implantable biotextiles, and there are always needs for designing and developing new types of yarns to improve the properties of biotextile implants. In the present study, we aim to develop novel nanofiber yarns (NYs) by combining nanostructure that more closely mimic the extracellular matrix fibrils of native tissues with biodegradability, strong mechanical properties and great textile processibility. A novel electrospinning syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…The directed conversion of electrospun nanofibers into yarn-like structure has opened a new window to manufacture innovative nanoyarns made from nanofibers with the diameters ranging from several to several hundred nanometers [ 3 , 4 ]. The electrospun nanoyarns with high specific surface area and high aspect ratio have been demonstrated to provide more cell adhesion sites in comparison with the traditional textile yarns made from micro-sized fibers (fiber diameter≥10 ​μm) [ 5 , 6 ]. Moreover, the nanofibers existed in the electrospun nanoyarns are found to effectively simulate the fiber scale and hierarchical structure of protein fibers in the native extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…The directed conversion of electrospun nanofibers into yarn-like structure has opened a new window to manufacture innovative nanoyarns made from nanofibers with the diameters ranging from several to several hundred nanometers [ 3 , 4 ]. The electrospun nanoyarns with high specific surface area and high aspect ratio have been demonstrated to provide more cell adhesion sites in comparison with the traditional textile yarns made from micro-sized fibers (fiber diameter≥10 ​μm) [ 5 , 6 ]. Moreover, the nanofibers existed in the electrospun nanoyarns are found to effectively simulate the fiber scale and hierarchical structure of protein fibers in the native extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…FTIR analysis was utilized to identify the functional groups and interactions of the MeGel and PLLA polymers within the fibers ( Figure 3 a). The PLLA nanofiber mats presented several characteristic peaks originating from the PLLA polymer, which mainly included ~1758 cm −1 (C=O stretching) and ~1186 cm −1 (–C–O stretching) [ 5 , 7 ]. The crosslinked MeGel nanofiber mats exhibited several characteristic peaks responsible for MeGel polymers, mainly ~1645 cm −1 (C=O stretching of amide I) and ~1526 cm −1 (N–H bending of amide II) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Electrospinning is a simple and versatile method used to directly spin polymeric solutions or melts into nanofibers, with diameters ranging from several to several hundred nanometers, which were at least 100 times thinner than fibers fabricated with traditional melt spinning and solution spinning [ 5 , 6 , 7 ]. Most recently, electrospun nanofibrous mats have found potential applications as wound dressing materials due to their high surface-to-volume ratio, small pore size, and high porosity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The field of medicine and tissue engineering appears to be especially promising. The works of Li et al [28] and Wu et al [69] demonstrated the robustness of nanofiber yarns enabling the processing of said yarns into woven material suited for cell scaffolds. Richard et al [70] used sutures made of electrospun PLLA yarns loaded with drugs, which showed sustained drug release and superior wound healing compared to controls.…”
Section: Discussionmentioning
confidence: 99%